Necessary and sufficient condition for the existence of positive solution to singular fractional differential equations - Wang, Y.; Liu, Lishan (SpringerOpen, 2015)
© 2015, Wang and Liu.In this paper, we discuss the existence of positive solution to singular fractional differential equations involving Caputo fractional derivative. Necessary and sufficient condition for the existence of C2[0,1] positive solution is obtained by means of the fixed point theorems on cones. In addition, the uniqueness results and the iterative sequences of the solution are also given.